PROGRAM PENGEMBANGAN USAHA PRODUK INTELEKTUAL KAMPUS (PPMU-PPUPIK): PRODUK TUNA NUT COOKIES - Sri Suro Adhawati; Sitti Fakhriyah; Suwarni Suwarni (LP2M Universitas Hasanuddin, 2019)
Abstract . PPUPIK is a multi-year community service program. The application form of the program is in the form of cookies business made from the best quality fresh tuna and peanuts. Product marketing uses the trademark O’SEA. Tuna nut cookies are cookies innovated from product development techniques, using simple technology, processed based on the standardization of processing hygiene and food safety quality standards. The purpose of activities is to earn income, place of learning, improve skills, create jobs, and create business opportunities for students and the community. The tuna nut cookis business is carried out within the campus. For quality control and product development activities, use the Fisheries Socio-Economic Entrepreneurship Laboratory of the Faculty of Marine and Fisheries (FIKP) Unhas. For production and marketing activities carried out in the Agribusiness and Entrepreneurship unit of FIKP Unhas. Production is carried out 3 times a week, 12 times a month and 144 times per year. The amount of main raw material is 1 kg of tuna for one production. The results of the implementation of activities show that the processed tuna nut cookies business has very good prospects. The success rate of sales is 99%, the business acceptance rate is 49.5%. Investment value of 13% per month. The RC-Ratio value is 1.7 greater than 1. The tuna nut cookies business is feasible to be developed.Keywords: Tuna cookies, production, marketing, revenueAbstrak. PPUPIK merupakan program pengabdian masyarakat multi tahun. Bentuk aplikasi program adalah berupa kegiatan usaha cookies yang dibuat dari ikan tuna segar kualitas terbaik dan kacang tanah. Pemasaran produk menggunakan merk dagang O’SEA. Tuna nut cookies merupakan cookies inovasi dari teknik pengembangan produk, menggunakan teknologi sederhana, diolah berdasarkan standarisasi pengolahan higienitas dan standar mutu keamanan pangan. Tujuan kegiatan untuk memperoleh pendapatan, wadah pembelajaran, meningkatkan keterampilan, menciptakan lapangan kerja, dan meciptakan peluang bisnis bagi mahasiswa dan masyarakat. Usaha tuna nut cookis dilakukan didalam kampus. Untuk kegiatan quality control dan pengembangan produk, menggunakan Laboratorium Kewirausahaan Sosial Ekonomi Perikanan Fakultas Ilmu Kelautan dan Perikanan (FIKP) Unhas. Untuk kegiatan produksi dan pemasaran dilakukan di unit Agribisnis dan Kewirausahaan FIKP Unhas. Produksi dilakukan 3 kali perminggu, 12 kali perbulan dan 144 kali pertahun, dengan jumlah bahan baku utama sebanyak 1 kg ikan tuna untuk satu kali produksi. Hasil pelaksanaan kegiatan memperlihatkan usaha olahan tuna nut cookies, memiliki prospek yang sangat baik. Tingkat keberhasilan penjualan 99%, tingkat penerimaan usaha sebesar 49.5%. Nilai investasi 13% per bulan. Nilai RC-Ratio sebesar 1.7 lebih besar dari 1. Usaha tuna nut cookies layak untuk dikembangkan.Kata Kunci: Cookies ikan tuna, produksi, pemasaran , pendapatan